Longevity-induced vertical innovation and the tradeoff between life and growth - Annarita Baldanzi; Klaus Prettner; Paul Tscheuschner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyze the economic growth effects of rising longevity in a framework of endogenous growth driven by quality-improving innovations. We show that a rise in longevity raises savings and thereby reduces the market interest rate. Since the monopoly profits generated by a successful innovation are discounted by the endogenous market interest rate, this raises the net present value of innovations, which, in turn, fosters R&D. The associated increase in the employment of scientists leads to faster technological progress and a higher long-run economic growth rate. From a welfare perspective, we show that the direct effect of an increase in life expectancy on lifetime utility is much larger than the indirect effect of the induced higher consumption due to faster economic growth. Consequently, the debate on rising health care expenditures should not predominantly be based on the growth effects of health care.
urn:nbn:de:bsz:100-opus-14199
Keywords: J11; J17; O31; O41; 330; long-run growth; vertical innovation; increasing life expectancy; welfare effects of changing longevity; size of health-care sectors